Investigation of the Influence of Different Camellia sinensis Teas on Kombucha Fermentation and Development of Flavored Kombucha with Brazilian Fruits - Raniele Oliveira Alves; Amanda Lins Bispo Monteiro; Camila Macaúbas da Silva; Tania Maria Sarmento da Silva; Rodrigo Lira de Oliveira; Camila Souza Porto; Tatiana Souza Porto (Beverages)
Teas derived from Camellia sinensis are traditionally used in kombucha fermentation, a process in which bacteria and yeasts play key roles. This study aimed to evaluate the effects of green, black, and white teas, as well as their combinations, on the physicochemical properties, antioxidant capacity, and total phenolic compound content of kombucha. In addition, the production of kombucha flavored with fruits. Statistical analysis of simplex centroid mixture design indicated that green tea promoted a positive increase in total phenolic content and antioxidant activities against ABTS and DPPH free radicals, being observed at 5868.46 µmol/mL, 705.40 µmol/mL, and 380.77 mg GAE/100 mL in the kombucha prepared using this tea individually. Then, six kombucha beverages were prepared from green tea, flavored with grape, caja, cashew apple, genipap, passion fruit, and tamarind. The phenolic profile analysis revealed the presence of twenty-six compounds, including twenty-five phenolics and one caffeine derivative. Among the beverages, tamarind-flavored kombucha stood out, exhibiting the highest total flavonoid content (156.77 mg EQ/g), which highlights the positive influence of tamarind on the bioactive properties of kombucha beverages. These results provide valuable insights to optimize kombucha production and explore the potential beneficial effects of flavored non-alcoholic beverages.